Improved saccharification of pilot-scale acid pretreated wheat straw by exploiting the synergistic behavior of lignocellulose degrading enzymes. Issue 87 (20th September 2015) - Agrawal, Ruchi; Gaur, Ruchi; Mathur, Anshu; Kumar, Ravindra; Gupta, Ravi Prakash; Tuli, Deepak K.; Satlewal, Alok
<x xml:space="preserve">Abstract</x> Improved saccharification by exploiting the synergism between biomass degrading enzymes.